FGF21 acting on the noradrenergic nervous system protects against influenza virus infection - Wei Fan; Yuan Zhang; Laurent Gautron; David G. Thomas; Heather W. Stout-Delgado; Edward J. Schenck; Tadiwanashe Gwatiringa; Kartik N. Rajagopalan; David J. Mangelsdorf; Steven A. Kliewer (Proceedings of the National Academy of Sciences, 2025)
The hormone fibroblast growth factor 21 (FGF21) is induced in murine liver in response to both bacterial and viral infection. In this report, we show that FGF21 is induced by infection with influenza virus in both humans and mice. Mice lacking FGF21 had decreased food intake, body weight, and body temperature compared to wild-type mice following influenza virus inoculation, indicating reduced tolerance to the infection. Conversely, pharmacologic administration of FGF21 after viral infection protected mice against these pathologic changes. Pair feeding studies showed that neither the induction of FGF21 nor the hypothermia was secondary to decreased food intake. Notably, mice selectively lacking FGF21’s coreceptor protein, βKlotho, in noradrenergic neurons were also more susceptible to influenza virus infection, including hypothermia. We show that FGF21 acting on noradrenergic neurons, including those in the locus coeruleus region, stimulates energy expenditure and thermogenic gene expression in brown adipose tissue. Our findings reveal an FGF21-regulated neuronal pathway that protects mice against influenza infection and suggest the potential utility of using FGF21 pharmacologically to improve outcomes after influenza infection.